IDENTIFIKASI PERUBAHAN MUTU TEMPE KEDELAI HASIL PERLAKUAN MICROWAVE OVEN, VACUUM PACKING, DAN COLD STORAGE - , THOMAS SEPTIAN H, Ir. Ag. Suryandono, M.App.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to obtain a longer storage-life for fermented soybean patty. Because with longer storage life, the small industry could grow, increasing their output to be distributed to other region, and preventing loss profit from decayed product before the product sold. The methods used in this research are cold storage, vacuum packing, and microwave oven. These three method will be compared with control (fermented soybean patty without any treatment) and based on SNI 3144 : 2009 about fermented soybean patty. Every fermented soybean patty that has been treated will be watched and analysed every 2 days. The test including chemical and physical characteristic. The chemical characteristics including water, ash, fat, and protein contents. Physical characteristic including color and smell. Fermented soybean patty is one of the food that is famous in Indonesia, especially in Java. With its high protein level, fermented soybean patty is wellknown as an organic high level protein source and is consumed by people as cheap protein source. Fermented soybean patty also has it disadvantages, its short storage-life and perishable. It's storage-life can be increased with various storage method. For a small industry it is best to use an everyday household, so that they should not spend much money. The example are refrigerator for cold storage, vacuum packing, and microwave oven to decrease the water content. The result showed that the best method to increase the storage-life of fermented soybean patty is cold storage using a refrigerator. And for fermented soybean patty with vacuum packing method is showing signs of decaying on day 8. While the storage-life of fermented soybean patty with microwave oven method is not different with the fermented soybean patty without any method (control), that is decaying on day 6.